ANALISIS PEMBELAJARAN MATEMATIKA BERBASIS LITERASI NUMERASI PADA MATERI PERKALIAN DI KELAS IV SD - Zikra, Fadila; Zaida Nurul Izzah; Adrias (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the lack of optimal mathematics learning based on numeracy literacy in multiplication materials in grade IV of elementary school. This study aims to describe the implementation of numeracy literacy learning in the Independent Curriculum and identify the obstacles faced in its implementation. The research uses a qualitative approach with a case study type. The subject of the study is a grade IV teacher of MIN Solok City. The data collection technique was carried out through online interviews and literature studies. The results of the study show that teachers integrate numeracy literacy through the Concrete-Pictorial-Abstract (CPA) and Realistic Mathematics Education (RME) approaches, non-routine questions, and supported using contextual problems and technology-based media. Implementation in the Independent Curriculum is carried out through differentiated and contextual learning. The main obstacle faced is the low reading comprehension and basic numeracy skills of students, which has an impact on difficulties in solving story problems and affects the success of the application of numeracy literacy in mathematics learning.